(untitled) (World Economics and Finance Bulletin, 2026)
Who receives state financial help reveals clear contrasts: universal access differs sharply from targeting low-income households. When downturns strike, outcomes shift based on whether relief favors breadth or precision. Data spanning more than fifty nations after 2000 highlights trends - Sweden’s model diverges from Brazil’s across inequality metrics, taxation effects, and shock absorption. Targeted spending may seem smarter, yet stumbles where bureaucracy drags. Universal programs, by contrast, ripple through communities, gaining strength during hardship. Efficiency isn’t always found in narrow rules. Though narrow plans may raise fewer individuals from poverty per dollar when targeting functions flawlessly, flawless systems rarely appear beyond rich countries. Mistakes often block eligible recipients, whereas bureaucracy drains resources set aside for aid. Thus, despite appearing more efficient in theory, practical barriers give broader inclusion an advantage. A method proving effective combines a uniform base transfer with additional sums tied to income level. Such a structure suits governments balancing limited spending against wide coverage. Old structures from the Soviet era now face review in certain regions. Because budgets tighten, shifts emerge - most clearly seen in Central Asia. Policy updates in Uzbekistan reshape decades-old aid programs. Success relies more on community specifics than abstract models. Reform keeps only what balances equity with spending limits